Comment on “Perturbation Analysis of the Nonlinear Matrix Equation ” - Maher Berzig; Erdal Karapınar (Abstract and Applied Analysis)
We show that the perturbation estimate for the matrix equation due to J. Li, is wrong. Our discussion is supported by a counterexample.